THE IMPACT OF TRAINING AND DEVELOPMENT ON ORGANIZATIONAL PERFORMANCE IN SHIPPING AGENCIES WITH REFERENCE TO THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Training is the process of helping a person increases his efficiency and effectiveness at work by enhancing and updating his professional knowledge, developing his personal skills applicable to his work, and cultivating in him appropriate behavior and attitude towards his work and the people he is working with. Development takes place as a result of training and generally entails growth plus change. Thus, training and development go hand in hand. The main aim is to gain a thorough understanding of the procedure for identifying, utilizing, and developing human capital for the benefit of the person and the organization in today’s highly dynamic and cutthroat business environment and examination of how training and development affect organizational performance. This thesis work's topic focuses on how employee training and development affect organizational performance. It was motivated by the observation that some businesses don't seem to care about enhancing employees' abilities but instead frown upon and penalize any flaws they display. Data has been collected from 120 respondents from the study area. Convenience sampling method is used while selecting the samples. The purpose of this paper is to study the impact of training and development on organizational performance in shipping agencies with reference to Thoothukudi district.